Antimicrobial Prophylaxis in Neonates and Children Undergoing Dental, Maxillo-Facial or Ear-Nose-Throat (ENT) Surgery: A RAND/UCLA Appropriateness Method Consensus Study - Erika Rigotti; Sonia Bianchini; Laura Nicoletti; Sara Monaco; Elena Carrara; Francesca Opri; Roberta Opri; Caterina Caminiti; Daniele Donà; Mario Giuffré; Alessandro Inserra; Laura Lancella; et al. (MDPI AG, 2022)
Surgical site infections (SSIs) represent a potential complication in surgical procedures, mainly because clean/contaminated surgery involves organs that are normally colonized by bacteria. Dental, maxillo-facial and ear-nose-throat (ENT) surgeries are among those that carry a risk of SSIs because the mouth and the first respiratory tracts are normally colonized by a bacterial flora. The aim of this consensus document was to provide clinicians with recommendations on surgical antimicrobial prophylaxis in neonates (<28 days of chronological age) and pediatric patients (within the age range of 29 days-18 years) undergoing dental, maxillo-facial or ENT surgical procedures. These included: (1) dental surgery; (2) maxilla-facial surgery following trauma with fracture; (3) temporo-mandibular surgery; (4) cleft palate and cleft lip repair; (5) ear surgery; (6) endoscopic paranasal cavity surgery and septoplasty; (7) clean head and neck surgery; (8) clean/contaminated head and neck surgery and (9) tonsillectomy and adenoidectomy. Due to the lack of pediatric data for the majority of dental, maxillo-facial and ENT surgeries and the fact that the recommendations for adults are currently used, there is a need for ad hoc studies to be rapidly planned for the most deficient areas. This seems even more urgent for interventions such as those involving the first airways since the different composition of the respiratory microbiota in children compared to adults implies the possibility that surgical antibiotic prophylaxis schemes that are ideal for adults may not be equally effective in children.